Simultaneous Acute Cardio-Cerebral Infarction: A Double Emergency Case, What Can Physicians Do Best In Rural Hospitals With Limited Facilities? - Prasiddha, Kaka Citta; Kurniawan, Chandra; Sudiyoko (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Highlights: 1. This case demonstrates the diagnostic and therapeutic challenges of simultaneous acute cardio-cerebral infarction in resource-limited settings. 2. Early recognition and hemodynamic-guided decision-making are crucial to optimize outcomes when both myocardial and cerebral infarction coexist. -- Abstract Background: Cardio-cerebral infarction (CCI) is a rare condition characterized by the simultaneous occurrence of acute myocardial infarction (AMI) and acute ischemic stroke (AIS), for which no standardized treatment strategy has been established. Case Summary: We report the case of a 72-year-old man who presented with left limb numbness for more than three hours and a brief episode of syncope 2.5 hours prior to admission. He had experienced persistent left-sided chest pain for two days. His medical history included hypertension and diabetes mellitus. On examination, the patient was fully conscious (GCS 15) with left-sided muscle weakness (grade 2) and a positive Babinski sign. The Siriraj score was −8.1. Brain computed tomography could not be performed due to limited facilities. Electrocardiography revealed non–ST-segment elevation myocardial infarction (NSTEMI), leading to a diagnosis of concurrent AIS and NSTEMI. Unfractionated heparin was administered to manage NSTEMI, while antiplatelet therapy was withheld pending neuroimaging. Chest pain improved after anticoagulation, but the patient was referred for further diagnostic evaluation and management. Based on the sequence of symptom onset, CCI in this case was most likely caused by cardiac pathology leading to cerebral infarction. Hemodynamic compromise associated with AMI may reduce cerebral perfusion, particularly in patients with long-standing hypertension. Conclusion: Management decisions in CCI should prioritize hemodynamic stability, continuous cardiac monitoring, and infarct location to determine the optimal treatment sequence